Analysis of Internal Factors Affecting the Implementation of Maturity Rating Policies in the Healthcare Public Service Agency of Indonesia - Arifin Indarto; Yos Sunitiyoso (Jurnal Syntax Admiration, 2024)
This study aims to address the gap in the literature by examining the internal factors affecting the implementation of maturity rating policies in Indonesian healthcare settings. This study employs a multimethod-qualitative approach in line with the adopted philosophy, enabling researchers to capture dynamic and contextual elements of organisational actual settings. This research draws several conclusions that are relevant to the implementation of business maturity policies, especially in the context of health care institutions in Indonesia. First, the implementation of the Maturity Rating policy has a significant impact on organizational governance, covering aspects of People, Process, and Technology. Benefits include managerial improvements, operational efficiency, compliance with legal requirements, and financial transparency and accountability. However, it is important to be aware of potential risks, especially conflicts of interest that can undermine objective evaluations.